Queer migration politics : activist rhetoric and coalitional possibilities - Chávez, Karma R. (Feminist media studies (University of Illinois (System). Press), 2013)
Delineating an approach to activism at the intersection of queer rights, immigration rights, and social justice, this work examines a series of "coalitional moments" in which contemporary activists discover and respond to the predominant rhetoric, imagery, and ideologies that signal a sense of national identity.